Issues and Concerns of Assessment for English Language Learners with Learning Disabilities - Pichardo, Blanca (Journal of the American Academy of Special Education Professionals, 2014)
Limited research has been accomplished within the past few years regarding issues and concerns of assessment for English Language Learners (ELL) with Learning Disabilities (LD). The increasing number of this unique population throughout schools has raised many concerns for professionals in education. English Language Learners with Learning Disabilities is a major topic that brings many issues and concerns of assessment for this particular population. How and by whom the students are being assessed is an immense concentration in the concerns of the topic. Assessment reliability and test fairness implies the issues educators have. Teacher readiness and student instructional history are two fundamental matters impacting special education outcomes of English Language Learners with LD.